The Dynamics of Indonesian Presidential Threshold: A Legal Perspectives - Rifqi Hamdani (Harmonization : Jurnal Ilmu Sosial, Ilmu Hukum, dan Ilmu Ekonomi, 2023)
Indonesian government was the result of a combination of presidential and parliamentary systems. According to the 1945 Constitution of the Republic of Indonesia, implementing a presidential system recognizes the President as an executive leader who is directly elected by the people. The election of the President and Vice President has an important role in government. To strengthen the presidential system, there steps were taken, such as setting thresholds in Article 222 of Law No. 7 of 2017 concerning public participation. This article described the requirements that must be met by political parties in nominating the President and Vice President based on Article 6A paragraph (2) of the 1945 Constitution. The minimum limit of votes that must be obtained by election participants to obtain certain rights in elections is called the threshold. The presidential threshold allows political parties to nominate candidates for President and Vice President as long as they come from political parties that won at least 20% of seats or 25% of valid votes nationally in previous legislative elections. This writing uses a normative juridical strategy and integrates conceptual methods by referring to laws, journals, books, and related research. The purpose of this writing is to identify regulations related to the Presidential Threshold in the context of organizing the vote for the President and Vice President based on Law No. 7 of 2017.